2000
DOI: 10.1038/sj.bjp.0703124
|View full text |Cite
|
Sign up to set email alerts
|

Bromoenol lactone enhances the permeabilization of rat submandibular acinar cells by P2X7 agonists

Abstract: 1 The permeabilizing e ect of P2X 7 agonists was tested in rat submandibular acinar cells using the uptake of ethidium bromide as an index. 2 The uptake of ethidium bromide by acini incubated at 378C in the presence of 1 mM ATP increased with time and reached after 5 min about 10% of maximal uptake measured in the presence of digitonin. 3 The response to ATP was dose-dependent (half-maximal concentration around 40 mM) and it was decreased when the temperature was lowered to 258C. 4 Benzoyl-ATP reproduced the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Previous work by us (6,10) and others (9,14,26,28) has shown that BzATP is as effective as 1 mM ATP in increasing [Ca 2ϩ ] i in salivary gland acinar and duct cells. In the present work, we found that 0.1 mM BzATP activated only a small inward current in acinar and duct cells, comparable with the current activated by 1 mM ATP, but much smaller than that activated by 5 mM ATP.…”
Section: P2rs In Parotid Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by us (6,10) and others (9,14,26,28) has shown that BzATP is as effective as 1 mM ATP in increasing [Ca 2ϩ ] i in salivary gland acinar and duct cells. In the present work, we found that 0.1 mM BzATP activated only a small inward current in acinar and duct cells, comparable with the current activated by 1 mM ATP, but much smaller than that activated by 5 mM ATP.…”
Section: P2rs In Parotid Glandmentioning
confidence: 99%
“…4, B and C). Brilliant Blue G (BBG) is a relatively specific P2X7R inhibitor (1,35) that was shown to inhibit P2X7Rs in parotid acinar cells (24,28). Fig.…”
Section: P2rs In Parotid Glandmentioning
confidence: 99%
“…Although the P2X 7 itself is considered as a nonselective large pore, some groups have had difficulty in detecting it in cells expressing the heterologous P2X 7 receptor, suggesting that the pore-forming molecule might be a distinct entity (11,14,77). Similarly, some cell types present a native P2 receptor that shares most of the P2X 7 receptor pharmacological features but fail to permeabilize (43,62).…”
mentioning
confidence: 99%
“…These results suggested that P2X7R could activate both calciumdependent and calcium-independent PLA2 in submandibular gland cells and epithelial cells. The iPLA2 was also associated with P2X7R permeabilization in submandibular gland acinar cells, and this permeabilization was inhibited by BEL [60]. In submandibular gland ductal cells, P2X7R induced kallikrein secretion in an iPLA2-dependent manner [28].…”
Section: P2x7r and The Lipid Metabolism Signaling Pathwaymentioning
confidence: 95%
“…In submandibular gland ductal cells, P2X7R induced kallikrein secretion in an iPLA2-dependent manner [28]. However, the data related to BEL in P2X7R-iPLA inhibition must be evaluated with caution because Chaid et al have described how BEL can enhance the permeabilization to ethidium bromide in submandibular acinar cells by acting directly on P2X7R [60].…”
Section: P2x7r and The Lipid Metabolism Signaling Pathwaymentioning
confidence: 99%